Physical Activity Intensity and Memory in Middle-Aged and Older Adults in China - Tang, Simi; Gao, Yucheng (Makara Journal of Health Research, 2026)
Background: Memory decline represents a major challenge in aging populations, and physical activity may help preserve cognitive function. However, evidence on whether different activity intensities are associated with memory remains inconclusive. Methods: Using five waves of the China Health and Retirement Longitudinal Study (2011–2020), this study investigated the association between physical activity intensity and memory among middle-aged and older adults in China. Individual fixed-effects models were applied to control for unobserved time-invariant heterogeneity. The outcome was memory score, and the main predictors encompassed high-, moderate-, and low-intensity physical activities. Results: Based on 52,135 person–wave observations from 21,423 individuals, high- and moderate-intensity physical activities were positively associated with memory performance, whereas low-intensity physical activity demonstrated no significant association. Males and females exhibited comparable patterns, with no statistically significant sex-specific difference. Conclusion: Moderate- and high-intensity physical activities are associated with better memory among Chinese middle-aged and older adults, supporting the promotion of physical activity as a strategy for healthy cognitive aging.